2009
DOI: 10.1007/s11096-009-9339-3
|View full text |Cite
|
Sign up to set email alerts
|

Statin prescribing in Northern Ireland and England pre and post introduction of the quality and outcomes framework

Abstract: Strategies should be considered to educate prescribers on cost-effectiveness by increasing their awareness of the negative budgetary impact resulting from early adoption of new and expensive statins and by encouraging generic prescribing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Prescription rates for antidepressants, statins, and other drugs have increased, but this increase is not clearly attributable to the QOF. [46][47][48] The costs of administering the scheme are substantial, and some staff are concerned that primary care has become more biomedical in focus and less patient centered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prescription rates for antidepressants, statins, and other drugs have increased, but this increase is not clearly attributable to the QOF. [46][47][48] The costs of administering the scheme are substantial, and some staff are concerned that primary care has become more biomedical in focus and less patient centered.…”
Section: Discussionmentioning
confidence: 99%
“…Prescription rates for antidepressants, statins, and other drugs have increased, but this increase is not clearly attributable to the QOF. [46][47][48] The costs of administering the scheme are substantial, and some staff are concerned that primary care has become more biomedical in focus and less patient centered.The QOF has strengthened team working and promoted a diversity of new roles, especially for nurses. Indeed, the QOF may have diminished the workload of general practitioners, enabled them to concentrate on more complex care, and led to teams in which work and knowledge is more distributed among its members.…”
mentioning
confidence: 99%
“… 20 Robust incentives such as the Quality Outcomes Framework (QOF) which rewards general practice for quality care have resulted in an increase in statin prescription across the UK. 21 Participation in the QOF is voluntary and almost all practices take part in it. In England, the use of lipid-lowering medication in a community cohort of adults aged 35 years and older who self-reported ischaemic heart disease or stroke was 79% in men and 72% in women in 2011.…”
Section: Discussionmentioning
confidence: 99%
“…We found no published studies on contraceptive prescribing trends during the time frame of the observed LARC increases against which to validate our estimates. Previous studies evaluating the effectiveness of QOF on prescribing of other drugs have shown similar increases in the volume of prescribing after the introduction of the QOF in both England and Northern Ireland compared to the period before[27]. Some have suggested that QOF may have rewarded and reinforced existing prescribing behaviours [28].…”
Section: Discussionmentioning
confidence: 92%